Hantavirus Expansion Trends in Natural Host Populations in Brazil. - Mello JHF; Muylaert RL; Grelle CEV (MDPI (Basel, Switzerland), 2024)
Hantaviruses are zoonotic agents responsible for causing Hantavirus Cardiopulmonary Syndrome (HCPS) in the Americas, with Brazil ranking first in number of confirmed HCPS cases in South America. In this study, we simulate the monthly spread of highly lethal hantavirus in natural hosts by conjugating a Kermack-McCormick SIR model with a cellular automata model (CA), therefore simultaneously evaluating both in-cell and between-cell infection dynamics in host populations, using recently compiled data on main host species abundances and confirmed deaths by hantavirus infection. For both host species, our models predict an increase in the area of infection, with 22 municipalities where no cases have been confirmed to date expected to have at least one case in the next decade, and a reduction in infection in 11 municipalities. Our findings support existing research and reveal new areas where hantavirus is likely to spread within recognized epicenters. Highlighting spatial-temporal trends and potential expansion, we emphasize the increased risk due to pervasive habitat fragmentation and agricultural expansion. Consistent prevention efforts and One Health actions are crucial, especially in newly identified high-risk municipalities.
Keywords: Andes Virus; Araraquara Virus; Juquitiba Virus; Necromys lasiurus; Oligoryzomys nigripes; SIR model; cellular automata; rodent-borne disease; Brazil; Orthohantavirus; Animals; Hantavirus Infections; Humans; Disease Reservoirs; Hantavirus Pulmonary Syndrome; Zoonoses